Regulation of Tomato Leaf Curl Viral Gene Expression in Host Tissues - Ian Dry; Les Krake; Phil Mullineaux; Ali Rezaian (Molecular Plant-Microbe Interactions, 2000)
The regulation of expression of the two virion-sense (V1 and V2) and four complementary-sense (C1, C2, C3, and C4) open reading frames (ORFs) of Tomato leaf curl virus (TLCV) was studied in both stably and transiently transformed Nicotiana tabacum tissues with fusions with the β-glucuronidase (GUS) reporter gene. GUS-expressing transgenic lines were obtained with each of the four complementary-sense gene-GUS fusion constructs and with truncated versions of the virion-sense gene-GUS fusion constructs (V1GUSΔC and V2GUSΔC) lacking complementary-sense sequences encoding the C1, C2, and C3 ORFs. However, little or no GUS expression was observed in kanamycin-resistant plants transformed with full-length, virion-sense gene constructs (V1GUS and V2GUS) constituting the complete viral genome. In contrast, V1GUS and V2GUS were found to direct high-level GUS expression in transient assays with tobacco protoplasts, suggesting that integration of viral constructs containing functional, complementary-sense genes may lead to repression or deletion of the introduced constructs in trans-genic tissues. V2GUS expression in the transient proto-plast assay was found to be severely curtailed by specific mutation of the C2 ORF, supporting a role for the C2 protein in transactivation of TLCV virion-sense gene expression. TLCV ORF-GUS constructs displayed distinctive tissue expression patterns in transgenic tobacco plants that could be divided into constitutive (C1, C4, and V2GUSΔC), predominantly vascular (C2, C3), or reduced expression in cells associated with the vascular bundles (V1GUSΔC). The significance of these results is discussed in terms of current models of gene function and regulation in geminiviruses.